How legislations affect new taxonomic descriptions. Issue 2 (February 2023) - da Silva, Manuela; Desmeth, Philippe; Venter, Stephanus N.; Shouche, Yogesh; Yurkov, Andrey
Abstract: Restrictions placed on the distribution of biological material by the legislation of countries such as India, South Africa, or Brazil exclude strains that could serve as type material for the validation or valid publication of prokaryotic species names. This problem goes beyond prokaryotic taxonomy and is also relevant for other areas of biological research.